Development of Alginate-Based Bacillus subtilis Biopellets for Tomato Bacterial Wilt Control - Sutthisa, Waraporn; Kaewpipat, Duangkamon; Wongkhomchang, Wannisa; Manphae, Apirada (Trends in Sciences, 2025)
Tomato bacterial wilt, caused by Ralstonia solanacearum, poses a significant challenge to crop production. This study screened 101 bacterial isolates from soil samples collected in Maha Sarakham Province, Thailand, for their antagonistic activity against R. solanacearum. The selection process involved initial screening based on visual inhibition zones using the paper disc diffusion method, followed by quantitative assessment of bacterial growth inhibition. Among the isolates, SK3-24 exhibited the highest inhibitory effect, forming an inhibition zone of 40.00 ± 17.32 mm, as measured using the standard zone of inhibition method, followed by SK3-20 (18.17 ± 1.50 mm). Morphological, biochemical, and molecular analyses (16S rRNA gene sequencing) identified SK3-24 as Bacillus subtilis. To enhance its application, SK3-24 was formulated into alginate-based biopellets, which maintained high bacterial viability (1.20 × 10⁸ CFU/g) after nine months of storage at 4 °C. Greenhouse trials demonstrated that these biopellets effectively suppressed disease incidence and severity in tomato seedlings and seeds. At 21 days post-inoculation, treated plants showed no disease symptoms and exhibited enhanced growth, with plant height (16.14 ± 1.32 cm) and leaf number (19.40 ± 1.34) comparable to healthy controls. These findings underscore the potential of SK3-24 biopellets as a sustainable and effective biocontrol strategy for managing tomato bacterial wilt while promoting plant health. HIGHLIGHTS This study explores the identification of effective antagonistic bacterial strains against R. solanacearum through 16S rDNA sequencing and aims to develop a bioformulation for sustainable management of tomato bacterial wilt. By integrating strain characterization, screening, and bioformulation development, this research seeks to deliver an environmentally friendly alternative to chemical pesticides, ensuring enhanced tomato production while safeguarding environmental and human health. GRAPHICAL ABSTRACT